Air pollution Dynamics: The role of meteorological factors in PM10 concentration patterns across urban areas - Carolina Girotti; Luiz Fernando Kowalski; Tiago Silva; Ezequiel Correia; Alessandra R. Prata Shimomura; Fernando Akira Kurokawa; António Lopes (City and Environment Interactions)
Air pollution is a major health problem in urban areas, influenced by traffic and atmospheric conditions. This study investigates the relationship between meteorological factors—wind direction, wind speed, boundary layer height, and atmospheric stability conditions —street trees, and PM10 concentration in three urban canyons: Avenida da Liberdade and Estrada de Benfica in Lisbon, and Marginal Tietê in São Paulo. Five years of hourly meteorological data and PM10 concentrations were analysed. Despite differences in scale and traffic volume, the results show that PM10 concentration patterns were similar in both Lisbon study areas. These areas also indicated a significant influence of atmospheric variables such as wind speed, boundary layer height, and atmospheric stability conditions. Tietê, with a higher vehicle density and different atmospheric conditions (lower wind speeds and greater atmospheric stability), presents higher PM10 peaks. Seasonal analysis revealed distinct patterns influenced by atmospheric instability, wind speed, and direction. In winter, areas with dense street tree cover had reduced PM10 levels, while those without showed higher concentrations due to increased stability. Wind direction played a crucial role, favouring the pollutant dispersal in canyons with parallel winds. The Factorial Analysis of Mixed Data method identified qualitative variables linked to the seasons, wind direction, and presence of trees. PM10 levels below the were associated with the summer and autumn period, parallel winds, and street trees, while levels above the limit were linked to winter period and areas without street trees. By integrating big data analytics with environmental monitoring, this research underscores the importance of considering the local atmospheric conditions and environmental variables in the urban air quality management. Thus, it demonstrates that the traffic volume alone does not determine PM10 concentrations; instead, the interplay of multiple factors, including meteorological conditions and urban planning, played a crucial role. This study provides valuable insights for developing effective strategies to mitigate urban air pollution and protect public health.